2017
DOI: 10.1088/1361-6587/aa8977
|View full text |Cite|
|
Sign up to set email alerts
|

An accurate and efficient laser-envelope solver for the modeling of laser-plasma accelerators

Abstract: Detailed and reliable numerical modeling of laser-plasma accelerators, where a short and intense laser pulse interacts with an underdense plasma over distances of up to a meter, is a formidably challenging task. This is due to the great disparity among the length scales involved in the modeling, ranging from the micron scale of the laser wavelength to the meter scale of the total laser-plasma interaction length. The use of the time-averaged ponderomotive force approximation, where the laser pulse is described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…The dashed black line is the theoretical result Eq. (19). The theoretical result is in good agreement with modeling for n b;0 =n 0 ≲ 2000 (corresponding to Γ ≲ 1).…”
Section: Expression For the Ion-motion Induced Emittance Growth Asupporting
confidence: 79%
See 2 more Smart Citations
“…The dashed black line is the theoretical result Eq. (19). The theoretical result is in good agreement with modeling for n b;0 =n 0 ≲ 2000 (corresponding to Γ ≲ 1).…”
Section: Expression For the Ion-motion Induced Emittance Growth Asupporting
confidence: 79%
“…Red dots are the simulation results, the black dashed line is the theoretical prediction Eq. (19). All the other bunch and plasma parameters are the same as in Fig.…”
Section: Equilibrium Bunch Distributions Enabling Ion Motion Withomentioning
confidence: 99%
See 1 more Smart Citation
“…17, the theoretical degradation is compared with modeling results obtained with the 2D-cylindrical particle-in-cell (PIC) code INF&RNO (using the quasi-static modality). 45,46 The following parameters, relevant to the LPA FEL application, 15 were used: L APL ¼ 2.9 cm, R APL ¼ 500 lm, h 0 ¼ 1 mrad, 250 MeV energy, n0 ¼ 0.49 lm, L b ¼ 2 lm, I b ¼ 4.5 kA (30 pC), I APL ¼ 750 A, and L drift ¼ 9.3 cm (thus r r ¼ 93 lm and beam density n b0 ¼ 1.7 Â 10 15 cm -3 ). One can observe in Fig.…”
Section: -5mentioning
confidence: 99%
“…This effect is exploited here by using laser pulses of length 8 ns that undergo considerable self-guiding during the pulse rise-time. MHD simulations performed using the multi-dimensional code MARPLE (Magnetically Accelerated Radiative PLasma Explorer) [23], with additional modules from inf&rno [24,25] to calculate the heater laser pulse propagation, showed that although the front of the heater pulse was mismatched to the plasma channel, later temporal slices of the pulse could be propagated with less than 10 % change in spot size.…”
mentioning
confidence: 99%